1999
DOI: 10.1016/s0008-6363(99)00257-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cardiac denervation affects the speed of coronary vascular regulation

Abstract: We conclude that the speed of response to metabolic and perfusion pressure changes is partly mediated by cardio-cardiac reflexes. Reflex coronary vasodilatation appears to reinforce the metabolic vasodilatation of a heart rate increase and oppose the vasoconstriction in response to increased perfusion pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…We also confirmed a trend towards smaller infarcts in dogs subject to extracardiac nerve ablation or pharmacologic decentralization using the autonomic ganglionic blocker hexamethonium bromide (Figure 3) [106]; these findings are also in agreement with earlier studies documenting increased tolerance to ischemic injury and a reduction in ventricular fibrillation threshold post-decentralization [102,107,108]. Reduced oxygen demand and improved perfusion of affected tissues could be responsible for increased ischemic tolerance of myocytes [43,104,105,109] in the absence of intact cardiac nerves. Of note, extracardiac surgical ablation of sympathetic and parasympathetic efferent neuronal inputs produces a decentralized (not denervated) heart without complete elimination of parasympathetic involvement [110,111]; on the other hand, pharmacologic ganglionic blockade with hexamethonium bromide blocks transmission within peripheral autonomic ganglia and vagal cardio-acceleration [112].…”
Section: Heartsupporting
confidence: 91%
See 1 more Smart Citation
“…We also confirmed a trend towards smaller infarcts in dogs subject to extracardiac nerve ablation or pharmacologic decentralization using the autonomic ganglionic blocker hexamethonium bromide (Figure 3) [106]; these findings are also in agreement with earlier studies documenting increased tolerance to ischemic injury and a reduction in ventricular fibrillation threshold post-decentralization [102,107,108]. Reduced oxygen demand and improved perfusion of affected tissues could be responsible for increased ischemic tolerance of myocytes [43,104,105,109] in the absence of intact cardiac nerves. Of note, extracardiac surgical ablation of sympathetic and parasympathetic efferent neuronal inputs produces a decentralized (not denervated) heart without complete elimination of parasympathetic involvement [110,111]; on the other hand, pharmacologic ganglionic blockade with hexamethonium bromide blocks transmission within peripheral autonomic ganglia and vagal cardio-acceleration [112].…”
Section: Heartsupporting
confidence: 91%
“…higher heart rate and LV systolic pressure) but stimulation with bradykinin produces a similar result without affecting LV pressure. On the other hand, Vergroesen et al documented that intact cardiac nerves were not essential for regulation of coronary blood flow [43]; however, they suggested that cardiac nerves essentially alter the speed of response of the coronary vascular bed to changes in heart rate and perfusion pressure. The cardiac nervous reflexes thought to be responsible for these effects has not been established but diverse cardiac afferent fibers and receptor subtypes (i.e.…”
Section: Vasoregulationmentioning
confidence: 99%
“…In the Spaan studies a step change in coronary artery pressure resulted in autoregulation of flow that was described by a mathematical model that represented a dependence on pressure and oxygen consumption rate. Interestingly, Vergroesen et al (37) observed that the speed of coronary vascular regulation was slowed by cardiac denervation. The present simulation is based on steadystate measurements and provides no information on the speed of the response.…”
Section: Validation Of Predicted Autoregulatory Functionmentioning
confidence: 99%
“…We also examined whether intact cardiac nerves were critical for coronary blood flow autoregulation; results confirmed a role for intrinsic cardiac neurons in autoregulatory control and myocardial perfusion even after ablation of extracardiac nerves from central nervous system control[26]. Ablation of external neuronal inputs to the heart also results in reduced myocardial efficiency that is consistent with impaired glucose utilization and depletion of cardiac catecholamine levels[27,28]; the latter directly affect myocardial oxygen demand[29-31]. Other animal studies reported that heterogeneity of myocardial perfusion is similar in innervated and denervated hearts[32-34]; possible explanations include: (1) the fact that regional denervation has little effect on vascular α-adrenergic receptors (in part due to circulating catecholamines); or (2) preserved neural modulation and autoregulation at different levels of the microcirculation across the ventricular wall[35,36].…”
Section: Coronary Blood Flow Regulation and Myocardial Perfusionmentioning
confidence: 94%